THE AESTHETICS OF COVID-19 WITHIN THE PANDEMIC OF THE CORONA CRISIS.: FROM LOSS AND GRIEF TO SILENCE AND SIMPLICITY – A PHILOSOPHICAL AND PASTORAL APPROACH - Louw, D.J. (Acta Theologica, 2020)
Within the corona crisis, the core question is: What is the impact of Covid-19 on the spiritual realm of meaning-giving, hoping and pastoral caregiving? How does it affect the realm of habitus and religious convictions, specifically when pastoral caregivers become involved? With reference to the human quest for wholeness in healing and helping, existing paradigms are critically analysed. What is meant by the aesthetics of Covid-19? A soulful movement within an aesthetic approach is discussed, i.e. from the ugliness of the pandemic to the beautification of the virus. Thus, the question is about the challenge how to grow and revisit the meaning dimension of life within a re-evaluation of the value of compassion. In this regard, the God-image of divine companionship, as framed by the ugliness of a “suffering God”, is discussed within the parameters of the praxis of hope care in pastoral ministry.